Participatory network mapping of an emergent social network for a regional transition to a low-carbon and just society on the Dingle Peninsula. Issue 12 (2nd December 2022) - Boyle, Evan; Ó Gallachóir, Brian; Mullally, Gerard
ABSTRACT: The paper develops a methodological approach that acts as a tool for active change agents working in community and just transition contexts to increase their capacity to engage a wider public in planning. An innovative contribution is made to the literature through the development of a participatory action research (PAR) based approach to social network analysis using a participatory mapping method with relation to sustainable transitions. The method comprises a participatory network mapping approach, adapted from the Net-Map toolkit, which is applied to a multi-stakeholder approach to realising a regional sustainability transition in the Republic of Ireland. Dingle Peninsula 2030 is an initiative aiming to transition a geographic region in the South West of Ireland to a low-carbon society by 2030 across the sectors of energy, agriculture, transport, education, employment, marine and tourism. Due to the scope of the overall project, a diverse range of stakeholders are involved. The method developed is used to undertake a qualitative collaborative social network analysis. The paper focuses on method, by analysing and reflecting upon the use of this participatory approach, in the initial stages of the overall project, in addressing complex sustainability and just transition challenges as they are revealed through a multi-stakeholder approach. Within this, the themes of participatory justice, social learning and visualising complexity are explored; and benefits and future improvements are outlined through reflections from both the researcher and the participant community.